أهمية الاقتصاد الأخضر في تعزيز الاستثمار الأجنبي المباشر بالتطبيق على مصر: The Importance of the Green Economy in Promoting Foreign Direct Investment in Application to Egypt - شادي إبراهيم شحاده (Journal of North African Economies, 2025)
The green economy is considered an economic model that aims to achieve economic development and protect the environment simultaneously, as it seeks to reduce pollution and depletion of natural resources. It thus contributes to preserving the environment and biodiversity. Foreign direct investment is the process of directing capital and productive resources from foreign investors to a country. Others, to establish new projects or expand existing projects in that country. In Egypt, World Bank data indicate a decline in foreign direct investment coming into Egypt as a percentage of GDP during the last years from 2018 to 2021. It declined from 3.10 to 2.80, 1.50, and 1.20. Respectively, therefore, the researcher aims to study the importance of the green economy in promoting foreign direct investment in Egypt from 1990-2021. The researcher relied in his methodology on the descriptive analytical approach and the quantitative approach by following the standard method and using time series. The study concluded that there is a statistical significance between the economy Green and foreign direct investment coming into Egypt.